Pacific Northwest Marine Sediments Contain Ammonia-Oxidizing Bacteria in the β Subdivision of the Proteobacteria - Nold, Stephen C. (American Society for Microbiology, 2000)
The diversity of ammonia-oxidizing bacteria in aquatic sediments was studied by retrieving ammonia monooxygenase and methane monooxygenase gene sequences. Methanotrophs dominated freshwater sediments, while β-proteobacterial ammonia oxidizers dominated marine sediments. These results suggest that γ-proteobacteria such as Nitrosococcus oceani are minor members of marine sediment ammonia-oxidizing communities.